Hybrid Energy Harvesting Applications of ZnO Nanorods for Future Implantable and Wearable Devices - Kathalingam Adaikalam; Hyun-Seok Kim (Micromachines)
The currently used electrical energy devices for portable applications are in limited life and need of frequent recharging, it is a big bottleneck for wireless and transportation systems. The scientific community is motivated to find innovative and efficient devices to convert environmental energy into useful forms. Nanogenerator can mitigate this issue by harvesting ambient energy of different forms into useful electrical energy. Particularly flexible nanogenerators can efficiently convert ambient mechanical energy into electrical energy which can be fruitfully used for self-powered sensors and electronic appliances. Zinc oxide is an interesting photosensitive and piezoelectric material that is expected to play a vital role in the synergetic harvesting of environmental thermal, sound, mechanical, and solar energies. As ZnO can be synthesized using easy methods and materials at low cost, the conversion efficiencies of solar and other energy forms can increase considerably. ZnO is a versatile material with interesting semiconducting, optical, and piezoelectric properties; it can be used advantageously to harvest more than one type of ambient energy. The coupled semiconducting and piezoelectric properties of ZnO are attractive for fabricating nanogenerators capable of harvesting both ambient optical and mechanical energies simultaneously. These nanolevel conversion devices are much required to power remote and implantable devices without the need for additional power sources. The present review briefly discusses the principles and mechanisms of different energy harvesting abilities of ZnO nanorods and their composites by consolidating available literature. In addition, the developments taking place in nanogenerators of different kinds—such as photovoltaic, piezoelectric, pyroelectric, and triboelectrics for self-powered technology—and their progress in hybrid energy harvesting application is reviewed.